Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Consider the difference of squares identity:
[tex]\[ a^2 - b^2 = (a + b)(a - b) \][/tex]

For the polynomial [tex]\(9x^2 - 49\)[/tex],
[tex]\[ a = \square \][/tex]
[tex]\[ b = \square \][/tex]


Sagot :

To solve the problem using the difference of squares identity [tex]\( a^2 - b^2 = (a + b)(a - b) \)[/tex], we first need to express the given polynomial [tex]\( 9x^2 - 49 \)[/tex] in the form [tex]\( a^2 - b^2 \)[/tex].

1. Start by comparing the given polynomial to the difference of squares form:
[tex]\[ 9x^2 - 49 \][/tex]

2. Identify the squares:
- [tex]\( 9x^2 \)[/tex] is a perfect square, and [tex]\( 9x^2 = (3x)^2 \)[/tex].
- [tex]\( 49 \)[/tex] is also a perfect square, and [tex]\( 49 = 7^2 \)[/tex].

3. So, we can write:
[tex]\[ 9x^2 - 49 = (3x)^2 - 7^2 \][/tex]

4. Now, we can see that it matches the identity [tex]\( a^2 - b^2 \)[/tex] where:
[tex]\[ a = 3x \quad \text{and} \quad b = 7 \][/tex]

Therefore, the values of [tex]\( a \)[/tex] and [tex]\( b \)[/tex] are:
[tex]\[ a = 3x \quad \text{and} \quad b = 7 \][/tex]